Female Friendships: Communities and Legacies of Women Readers and Women Writers in Ana Plácido and Guiomar Torresão - Vieira, Estela (Revista de Escritoras Ibéricas, 2020)
ABSTRACT: This essay will focus on two nineteenth-century Portuguese women writers, Ana Plácido (1831-1895) and Guiomar Torresão (1844-1898). Women’s writing in Portugal before 1900 remains vastly understudied. This essay aims to remedy this historical neglect by analyzing and reading two decisive works by these writers, Plácido’s Herança de lágrimas (1897) and Torresão’s Uma alma de mulher (1869). While attempting to integrate their writing into canonical and feminist traditions and situate their work in the shifting frameworks of romanticism, I examine how these novels build through complex plot twists and narrative structure, communities of women readers, writers, and intellectuals. These figures, whether fictional or real, serve as companions for the female characters and the women writers. In both of these neglected works we see how the authors privilege female solidarity, building a consciousness of a legacy of women writers, readers, and intellectuals that albeit mostly fictional resound to contradict the idea that women played a minor role in the Lusophone nineteenth-century literary milieu. While following certain conventions of romanticism these works suggest through their narrative devices and structure alternatives for their female protagonists, and thus challenge definitions of the romantic genre and of the romance plot while at the same time questioning the limitations on women’s social and intellectual roles. RESUMEN: Este artículo estudia dos escritoras portuguesas del siglo XIX, Ana Plácido (1831-1895) y Guiomar Torresão (1844-1898). La escritura de mujeres portuguesas anterior a 1900 sigue contando con muy pocos estudios. Este artículo se propone paliar esa carencia historiográfíca por medio del análisis y la lectura de dos obras clave de escritoras de ese período: Herança de lágrimas (1897) de Plácido y Uma alma de mulher (1869) de Torresão. Aunque se procura integrar su producción en las tradiciones canónica y feminista y situar su obra en el contexto fluctuante del romanticismo, se estudia cómo en esas novelas se crean, a través de giros complejos de la trama y de las estructuras narrativas, comunidades de lectoras, escritoras y mujeres intelectuales. Estas figuras, ya sean ficticias o reales, acompañan a los personajes femeninos y a las escritoras. En estas dos obras ignoradas se observa cómo las autoras subrayan la solidaridad femenina y crean conciencia de un legado de escritoras, lectoras e intelectuales en femenino que, siquiera en la ficción, contribuyen a combatir la idea de que las mujeres desempeñaron un papel menor en el ambiente literario luso del siglo XIX. Aunque siguen algunas convenciones románticas, estas obras, por medio de sus técnicas narrativas y de sus variantes estructurales, proponen alternativas para sus protagonistas femeninas, con lo que desafían las definiciones del género romántico y la trama novelesca, a la par que cuestionan las limitaciones en los roles sociales e intelectuales de las mujeres.